Negócios criativos em comunidades periféricas e seus impactos no desenvolvimento local : o caso do Bar do Omar no Rio de Janeiro - Silva, Rafael de Mello (2024)
This dissertation aims to investigate the impact of creative businesses in peripheral communities, focusing on Bar do Omar, located in Morro do Pinto, Rio de Janeiro. The main objective is to identify the management challenges of Bar do Omar and its impact on local development. The research employs a mixed-methods approach with in-depth interviews and structured questionnaires. The results show that Bar do Omar acts as a transformative agent in the local community, promoting social inclusion, generating jobs, and valuing local culture, significantly contributing to cultural tourism in the region. The management faces challenges such as lack of infrastructure, financial difficulties, and the need to adapt to market demands. The research highlights the importance of public support policies and collaboration among local establishments. It concludes that microenterprises in peripheral contexts can be catalysts for social and economic change. The integration of public policies and grassroots initiatives can amplify the positive impact of enterprises like Bar do Omar, promoting inclusive and sustainable development